EVALUATION OF INDONESIAN TEXTBOOK USING ENGLISH LANGUAGE TEACHING CHECKLIST FOR THE TEN GRADERS SENIOR HIGH SCHOOL (RETAIN, 2020)
A textbook is an essential part of English language teaching. In assuring the quality, the objectives of this present study are to find the quality and provide a qualitative evaluation of the general elements and teaching-learning content of the textbook entitled “Bahasa Inggris SMA/MA/SMK/MAK Kelas X 2017 revision.” This study focuses on the layout and the congruency aspect of the textbook with the curriculum and used reliable instruments of an English language teaching evaluation checklist and Indonesian national standard in analyzing the data. The present study uses a textbook analysis descriptive qualitative method in analyzing the data. The researcher gathered the data by gathering the textbook and the instruments, familiarize the data, coding, and select snapshots of the textbook. In-depth qualitative document analysis was conducted to gather the description of the material evaluation. The findings of this study reveal that the quality of the textbook has high usefulness with a score of (M= 2. 9). Additionally, the researcher also describes the qualitative implication of the evaluation checklist. The finding of the study is expected to be useful for the teacher and instructional designer in making a future decision of the textbook.